Systematic Review of the Economic Evaluation of Returning Incidental Findings in Genomic Research - Fontes Marx, Mayara; Ataguba, John E.; Vries, Jantina de; Wonkam, Ambroise (Frontiers in Public Health, 2021)
Objectives: Discussions regarding who and how incidental findings (IFs) should be returned and the ethics behind returning IFs have increased dramatically over the years. However, information on the cost and benefits of returning IFs results to patients remains scanty. Design: This paper systematically reviews the economic evaluation of returning IFs in genomic sequencing. We systematically searched for published articles on the cost-effectiveness, cost-benefit, cost and cost-utility of IFs in Medline, Scopus, PubMed, and Google Scholar. Results: We found six published articles that met our eligibility criteria. Two papers used cost analysis only, one used cost-benefit analysis only, two used both cost analysis and cost-effectiveness, and one used both cost-benefit analysis and cost-utility to describe the cost of returning IFs in genomic sequencing. Conclusion: While individuals value IF results and are willing to pay for them, the cost of returning IFs depends on the primary health condition of the patient. Although patients may be willing to pay, there was no clear evidence that returning of IFs might be cost-effective. More rigorous economic evaluation studies of IFs are needed to determine whether or not the cost of returning IFs is beneficial to the patient. Keywords: Genomics; Incidental findings (IFs); Economic evaluation; cost-effectiveness